Muscle damage after a simulated tennis match in young tennis players - Santos, R. O.; Gomes, R. V.; Nosaka, K.; Moreira, A.; Aoki, M. S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The present study investigated changes in indirect markers of muscle damage following a simulated tennis match using nationally ranked young (17.6 ± 1.4 years) male tennis players. Methods: Ten young tennis players played simulated matches in which each player had three one-hour matches against three players on outdoor red clay courts following the International Tennis Federation rules. Muscle soreness, plasma creatine kinase activity (CK), serum myoglobin concentration (Mb), one repetition maximum (1RM) squat strength, and squat jump (SJ) and counter movement jump (CMJ) heights were assessed before, immediately after, and 24 and 48 hours after the matches. Results: A one-way repeated measures ANOVA and post-hoc Tukey test revealed significant but small increases in muscle soreness, CK and Mb at 24-48 hours post-match, and decreases in 1RM squat strength (-35.2 ± 10.4%), SJ (-7.0 ± 6.0%) and CMJ (-10.0 ± 6.3%) heights immediately post-match (p<0.05). At 24 hours post-match, the 1RM strength and jump heights were not significantly different from the baseline values for the average, but several players showed lower values of these measures and required another day for the full recovery. Conclusion: The simulated tennis match induced mild muscle damage, but tennis players could recover in 48 hours.